Administrative procedure and administrative legal proceedings within of the adopted Administrative Procedural and process-related Code of the Republic of Kazakhstan - Zavotpaeva, A.T.; Kussainova, A.K. (Bulletin of the Karaganda University “Law Series”, 2021)
This article is devoted to the analysis of adopted Administrative Procedural and process-related Code of the Republic of Kazakhstan, the introduction of which is expected from 1 July 2021. The purpose of this article is to consider innovations in administrative procedure and administrative legal proceedings within the frame work of the adopted Administrative Procedural and process-related Code of the Republic of Kazakhstan. During the research general scientific, private scientific, and legal methods of cognition were used. The article explores the concept of an administrative process. The introduction of the adopted Administrative Procedural and process-related Code will introduce changes in administrative procedure and its application. State bodies will have to bring normative legal acts into compliance, including on the procedure for consideration of References Individuals and Legal Entities. The Administrative Procedural and process-related Code changes the perception of administrative legal proceedings in its current understanding. Administrative proceedings will become an effective administrative justice.